Expanding the use of internal mammary artery perforators as a recipient vessel in free tissue transfer: An anatomical analysis by computed tomography angiography in breast cancer patients. Issue 6 (4th March 2019) - Shin, Dongwoo; Sung, Ki Wook; Fan, Kenneth L.; Park, Tae Hwan; Song, Seung Yong; Roh, Tai Suk; Lew, Dae Hyun; Lee, Dong Won
Abstract : Background: The internal mammary artery (IMA) perforator has assumed recent prominence as recipient vessels in free autologous breast reconstruction. However, anatomical understanding is unclear, due to limited cadaver and clinical studies. We evaluated the usability of these vessels by evaluating perforator size, dominance, laterality, interspace location, and relationship with breast volume. Methods: A retrospective review assessed 197 female patients with breast cancer who had undergone computed tomography angiography (CTA) of the chest wall. The average age and body mass index (BMI) of patients was 49.0 ± 6.5 years and 24.2 ± 5 .8 kg/m 2, respectively. The average volume of breasts was 437 ± 190 mL. Our analysis focused on the anatomy of IMA perforator and its relationship to volume and BMI. Results: A total of 377 hemi‐chest evaluations were performed. Most patients (95.5%) had sizeable perforating artery identified on CTA. Among all sizeable perforators identified, the mean diameter of the most dominant arterial perforator was 1.8 ± 0 .8 mm. The right hemi‐chest had significantly larger perforators than the left (1.9 ± 0 .9 mm vs. 1.7 ± 0 .7 mm, p  = 0.002). The first intercostal space (ICS) had a slightly greater of perforators than second ICS (34.6% vs. 29.8%, p  = 0.172). However, second ICS had a greater number of most dominant perforators compared to first ICS (38.9% vs. 34.7%, p  = 0.357). Perforators from first ICS emerge medial to the sternal edge and breast footprint. When dividing groups with 0–1 versus 2–3 reliable perforators, breast volume was significantly higher in the later (422.0 mL vs. 461.2 mL, p  = 0.019). Conclusion: These results are expected to encourage microsurgeons to use the IMA perforator by providing a clear anatomical roadmap.